Pengaruh Penambahan Level Jus Tape Singkong Terhadap Kualitas Fisik Dan Kadar pH Silase Daun Tebu (Saccharum Officinarum L.) - Putri, RR Ningrum Della Septian Klessy; Lestari, Dian; Putra, Boby Arya; Bilyaro, Woki; Falah, Reo Radius (Universitas Muhammadiyah Kotabumi, 2024)
This research aims to determine the potential of sugarcane leaf waste as animal feed and the addition of certain substances as starter bacteria, namely cassava tape juice which contains high levels of carbohydrates so that it can meet the nutritional needs of BAL during the fermentation period. The use of tape juice on the physical quality (aroma, color, texture) and pH levels of sugarcane leaf silage. This research is an experimental study using a completely randomized design (CRD) method consisting of 4 treatments and 5 replications. The treatments that will be applied are P0 (sugarcane leaves + 0% cassava tape juice), P1 (sugarcane leaves + 3% cassava tape juice), P2 (sugarcane leaves + 6% cassava tape juice), P3 (sugarcane leaves + cassava tape juice 9%), data analysis using Anova (Analysis of Variance) and if the data results are real, they are further tested with DMRT (Duncan Multiple Range Test). The research results showed that the addition of cassava tape juice did not improve the physical quality (aroma, color, texture) of silage and pH levels.